A CASE STUDY OF IMPLEMENTING DIFFERENTIATED INSTRUCTION IN SOCIAL STUDIES TEACHING AT A JUNIOR HIGH SCHOOL IN BANYUWANGI - Sasi Andriani (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The objective of this article is to examine a case study on the utilization of differentiated learning approach in teaching at a Junior High School located in the Singojuruh District, Banyuwangi, East Java. The author employs a case study as a research method grounded in an interpretive paradigm. The participants in this study are 30 seventh-grade students. They were requested by the school principal to engage in a demonstration of differentiated instruction alongside one of the teacher facilitators from Banyuwangi Regency. Data were collected through pre-observation interviews, direct observations, and post-observation interviews. The research findings indicate that well-designed lessons using the differentiated learning approach can provide maximum benefits for students with varying levels of abilities. Moreover, this approach also enhances student engagement in the classroom learning process. Additionally, this study also offers several suggestions for future research.